Study on Urban Trees in Ekiti State University, Ado Ekiti, Nigeria: 1. Structure and Composition - Iyanuoluwa Kikelomo Ajayi; Joshua Kayode; Benson Oluwafemi i Ademiluy (Budapest International Research and Critics University, 2020)
An inventory of tree biodiversity was carried in Ekiti State University, Ado-Ekiti, Nigeria, which is an institution where ecological and economic roles of trees are disseminated. The study involved the use of a stratified sampling technique to carry out a survey of trees species in the University. The campus was divided into four strata - Road side (A), Car parks (B), Office area (C), Student halls/ religion area (D) - and each stratum was further sub-divided into sub-strata. All the trees within each sub-stratum were identified to species level with their scientific, local and family names and they were counted and recorded. The relative frequency, relative density and relative abundance of the identified species were determined. Similarities indices and indices of diversity were determined on the tree species sampled among the strata. The results obtained revealed that a total of 27 tree species, belonging to 17 families were sampled in the campus. The family Caesalpiniaceae has the highest number of species. Some of the identified tree species were found in multiple and dual strata while some occurred in only one stratum. A total of 838 tree individuals were obtained. The most frequently occurring species were T. grandis, G. arborea and P. longifolia with 298, 181 and 149 individuals respectively. The indices of similarities among the strata were low. However Strata A and B as well as A and C appeared to be similar in tree composition. Strategies that would improve and maintain tree composition in the University campus were proposed